Individualized hydration plans improve performance outcomes for collegiate athletes engaging in in-season training - David Ayotte; Michael P. Corcoran (Taylor & Francis Group, 2018)
Background Athletes commonly consume insufficient fluid and electrolytes just prior to, or during training and competition. Unlike non-athletes or athletes who do not engage in frequent rigorous and prolonged training sessions, "hard trainers" may require additional sodium and better benefit from a hydration plan tailored to their individual physiology. The purpose of this randomized cross-over study was to determine whether a hydration plan based off of an athlete's sweat rate and sodium loss improves anaerobic and neurocognitive performance during a moderate to hard training session as well as heart rate recovery from this session. Methods Collegiate athletes who were injury free and could exercise at ≥ 75% of their maximum heart rate for a minimum of 45 min were recruited for this randomized, cross-over study. After completing a questionnaire assessing hydration habits, participants were randomized either to a prescription hydration plan (PHP), which considered sweat rate and sodium loss or instructed to follow their normal ad libitum hydration habits (NHP) during training. Attention and awareness, as well as lower body anaerobic power (standing long jump) were assessed immediately before and after a moderate to hard training session of ≥ 45 min. Heart rate recovery was also measured. After a washout period of 7 days, the PHP group repeated the training bout with their normal hydration routine, while the NHP group were provided with a PHP plan and were assessed as previously described. Results Fifteen athletes from three different sports, aged 20 ± 0.85 years, participated in this study. Most participants reported feeling somewhat or very dehydrated after a typical training session. Compared to their NHP, participants following a PHP jumped 4.53 ± 3.80 in. farther, tracked moving objects 0.36 ± 0.60 m/second faster, and exhibited a faster heart rate recovery following a moderate to hard training session of 45-120 min in duration. Conclusion A tailored hydration plan, based on an athlete's fluid and sodium loss has the potential to improve anaerobic power, attention and awareness, and heart rate recovery time.